Stability analysis of maize hybrids under different agro-ecological zones of Odisha, India - Lenka, Devraj; Das, Sindhusnata; Swain, Digbijaya; Lenka , Devidutta; Tripathy , Swapan K (Bangladesh Journal of Botany, 2023)
Thirty maize hybrids were evaluated for stability of yield performance across six locations of Odisha using the additive main effect and multiplicative interaction (AMMI) model. The analysis of variance revealed significant difference among genotypes, environments, G x E interactions, IPCA I, IPCA II and IPCA III scores. Among the high yielding genotypes, ZH17210, ZH159, ZH17223, P3502 and ZH161418 recorded low interaction, 28(ZH159) and 2(ZH161418) exhibited positive interactions (both IPCA 1 and IPCA II had same sign) and 6(ZH17223) revealed negative interaction. Koraput location(E6) was found to be most favorable environment while Banjanagar (E2) indicated as a poor environmental condition for grain yield. Bhubaneswar location with IPCA I and IPCA II scores close to zero seems to have minimum environmental interaction for grain yield. Among the hybrids; ZH17229), VH151139 and ZH161418 showed higher grain yield and minimum interaction (IPCA I) and hence, may be considered most stable. In contrast, the highest yielding hybrid ZH17210 demonstrated differential yield performance over environment and appreciably higher magnitude of G x E interaction (IPCA I) indicating adaptation to specific environment. Bangladesh J. Bot. 52(1): 1-8, 2023 (March)